AlCrN / TiAlSiCuN nano composite coating as well as preparation method and application thereof
By adopting the AlCrN/TiAlSiCuN nanocomposite coating structure in the PVD hard coating and combining the design of the CrN transition layer, the shortcomings of the existing coating in many properties are solved, and higher toughness, lubricity, thermal stability and binding strength are achieved.
Patent Information
- Application Number
- CN202411973597.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The existing PVD hard coating still has room for improvement in lubrication, wear resistance, toughness, coating bond strength and thermal stability.
Using the AlCrN/TiAlSiCuN nanocomposite coating structure, multiple properties of the coating are improved by alternately setting up the AlCrN and TiAlSiCuN coatings and depositing a CrN transition layer on the substrate surface.
It significantly improves the toughness, lubricity, thermal stability of the coating, and enhances the bonding strength between the film layers while maintaining a high level of hardness.
Smart Images

Figure CN119710545A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PVD hard coatings, and in particular to an AlCrN / TiAlSiCuN nanocomposite coating and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern manufacturing industry, hard coating has been paid much attention as an important part of domestic materials science and is widely used in the fields of machinery, medicine, textile, microelectronics, aviation, etc. Hard coating means depositing a layer of coating of several microns on the substrate while maintaining the substrate unchanged, so that the parts can obtain a longer service life. After the hard film layer is deposited on the tool, the cutting performance of the tool is improved, the processing quality of the tool cutting is improved, and its processing cost is greatly reduced, and its hardness and toughness are greatly improved.
[0003] With the rapid development of dry cutting, the emergence of PVD hard coating has greatly made up for this deficiency. Tool coating technology can be divided into multi-element coating, gradient coating, nano-composite coating, nano-multilayer coating, etc. with the development of time. The performance of its coating has also been steadily improved and applied in various cutting processing environments. Physical vapor deposition technology is the process of using a large current to evaporate the target material or bombard the target surface with additional particles so that the target particles are sputtered to the substrate surface to achieve deposition. Physical vapor deposition technology mainly includes evaporation, magnetron sputtering (MS), ion plating (AIP) and electron beam physical vapor deposition technology. Physical vapor deposition technology has been quite perfect in China. The composite coating structure prepared by this technology has been proved to effectively improve the performance of the coating, such as TiAlN / AlCrN, AlCrSiN / AlCrN, etc. However, its lubrication, wear resistance, toughness, coating bonding strength and thermal stability need to be further improved.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide an AlCrN / TiAlSiCuN nanocomposite coating and a preparation method and application thereof, and to use a TiAlSiCuN coating and an AlCrN coating to form a multilayer composite coating structure, thereby improving the toughness, lubricity and thermal stability of the coating and the bonding strength between film layers, while also not reducing the hardness of the coating due to the addition of Cu.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention provides an AlCrN / TiAlSiCuN nanocomposite coating, which is coated on a substrate and comprises, from the surface of the substrate outward, a CrN transition layer, and an AlCrN coating and a TiAlSiCuN coating arranged alternately;
[0008] The AlCrN coating and the TiAlSiCuN coating are at least one layer respectively;
[0009] In the CrN transition layer, Cr accounts for 45-50% and N accounts for 50-55% in terms of atomic percentage;
[0010] In the AlCrN coating, Al accounts for 23-27%, Cr accounts for 10-14%, and N accounts for 59-67% in terms of atomic percentage;
[0011] In the TiAlSiCuN coating, according to atomic percentage, Ti accounts for 18-20%, Al accounts for 35-39%, Si accounts for 5-8%, Cu accounts for 6-8%, and N accounts for 25-36%.
[0012] Furthermore, the thickness of the CrN transition layer is 0.1-0.3 μm;
[0013] And / or, the total thickness of the AlCrN coating is 1.2-1.6 μm; preferably, the thickness of the AlCrN coatings disposed at different positions is the same;
[0014] And / or, the total thickness of the TiAlSiCuN coating is 1.2-1.6 μm; preferably, the thickness of the TiAlSiCuN coatings arranged at different positions is the same;
[0015] And / or, in each group of AlCrN coating and TiAlSiCuN coating formed outward from the CrN transition layer, the thickness ratio of the AlCrN coating to the TiAlSiCuN coating is 1:1.
[0016] Furthermore, the TiAlSiCuN layer of the AlCrN / TiAlSiCuN nanocomposite coating forms a nanocomposite structure in which the amorphous phase Si3N4 encapsulates the (Ti, Al)N nanocrystalline phase.
[0017] The second aspect of the present invention provides a method for preparing the AlCrN / TiAlSiCuN nanocomposite coating according to the first aspect, comprising the following steps:
[0018] S1. Pretreatment: Grind and polish the substrate, clean and wipe off dust;
[0019] S2. Vacuuming: Pump the pressure in the coating chamber to 3×10 -3 ~4×10-3 Pa, and then the temperature in the coating chamber is raised to 480°C before coating begins;
[0020] S3, etching and cleaning: introduce argon gas into the coating chamber, control the pressure in the coating chamber to 0.3-1 Pa, turn on the etching target to etch particles;
[0021] S4. TiAlSiCuN / AlCrN / CrN layer deposition: open the argon channel to pass argon gas, then open the nitrogen channel to pass nitrogen gas, set the bias voltage to -80~120V, adjust the pressure in the coating chamber to 0.8~1Pa, turn on the Cr target, deposit to obtain a CrN coating, then alternately turn on the AlCr target and the TiAlSiCu target, turning on the AlCr target and the TiAlSiCu target once each is counted as one cycle, the cycle is at least once, and a TiAlSiCuN / AlCrN nanocomposite coating is deposited.
[0022] Furthermore, in the step S1, the substrate is any one of cemented carbide, high speed steel, and corundum.
[0023] Furthermore, in step S1, the grinding and polishing treatment is to use sandpaper to grind the substrate until it is smooth and flat without obvious defects, and then use a metallographic polishing machine to polish until the surface of the substrate sample is mirror-like without obvious defects; and / or, the cleaning is first ultrasonic cleaning in an acetone solution, and then cleaning in ultrapure water and anhydrous ethanol; and / or, the wiping of dust is wiping with anhydrous ethanol.
[0024] Further, in step S3, the etching target is a Ti target, the current of the Ti target is 80-100A, and the etching negative bias is -120--180V; and / or, the particle etching time is 110-130min; and / or, the flow rate of the argon gas is 450-500sccm.
[0025] Further, in step S4, the target current of the Cr target is 80-100A; and / or, the target current of the AlCr target is 80-100A; and / or, the TiAlSiCu target is a mosaic target, and its target current is 80-100A;
[0026] and / or, the flow rate of the argon gas is 40 to 60 sccm, and the flow rate of the nitrogen gas is 600 to 800 sccm;
[0027] And / or, the number of cycles is four.
[0028] Further, the AlCr target material is composed of the following components in atomic percentage: Al 70-75% and Cr 25-30%, preferably Al 70% and Cr 30%;
[0029] And / or, the TiAlSiCu target material is composed of the following components in atomic percentage: Ti 18-25%, Al 55-65%, Si 8-12%, Cu 8-10%, preferably Ti 22%, Al 60%, Si 10%, Cu 8%.
[0030] The third aspect of the present invention provides use of the AlCrN / TiAlSiCuN nanocomposite coating described in the first aspect or the AlCrN / TiAlSiCuN nanocomposite coating prepared by the preparation method described in the second aspect in a cutting tool.
[0031] The AlCrN / TiAlSiCuN nanocomposite coating provided by the present invention has the following beneficial effects:
[0032] (1) TiAlSiCuN / AlCrN / CrN coating has a low friction coefficient and strong film-base bonding strength;
[0033] (2) TiAlSiCuN / AlCrN / CrN coating is a nanocomposite coating. The amorphous phase contained in the coating has the function of preventing cracks from occurring and inhibiting the movement of dislocations, thus greatly improving the toughness of the coating.
[0034] (3) TiAlSiCuN / AlCrN / CrN coating is a composite of AlCrN coating and CrN coating on the basis of TiAlSiCuN coating, which not only improves the thermal stability of the coating, but also improves the bonding strength between the film layers;
[0035] (4) TiAlSiCuN / AlCrN / CrN coating introduces Cu element on the basis of TiAlSiN coating, which plays an important role in reducing the internal pressure stress of the hard coating and reducing the friction coefficient. The deposited TiAlSiCuN film is composed of nanocrystalline AlCrN, Cu, and amorphous silicon nitride;
[0036] (5) The TiAlSiCuN / AlCrN / CrN coating process has high repeatability and good self-lubricating effect, which plays an important role in protecting the ecological environment;
[0037] (6) Arc ion plating technology is used to deposit TiAlSiCuN coating on the substrate surface, and the coating surface is denser and smoother. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 A schematic diagram of the structure of a TiAlSiCuN / AlCrN / CrN coating provided in Example 1 of the present invention;
[0040] Figure 2 Surface morphology of the TiAlSiCuN / AlCrN / CrN coating provided in Example 1 of the present invention;
[0041] Figure 3 This is a graph of the average friction coefficient of the TiAlSiCuN / AlCrN / CrN coating provided in Example 1 of the present invention and the AlCrTiSiN / CrN composite layer provided in Comparative Example 1. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0043] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0044] The TiAlSiCuN / AlCrN / CrN coating of the present invention is the AlCrN / TiAlSiCuN nanocomposite coating provided by the present invention.
[0045] According to a first aspect of the present invention, the present invention provides an AlCrN / TiAlSiCuN nanocomposite coating, which is coated on a substrate and comprises, from the surface of the substrate outward, a CrN transition layer, and an AlCrN coating and a TiAlSiCuN coating arranged alternately;
[0046] The AlCrN coating and the TiAlSiCuN coating are at least one layer respectively;
[0047] In the CrN transition layer, Cr accounts for 45-50% and N accounts for 50-55% in terms of atomic percentage;
[0048] In the AlCrN coating, Al accounts for 23-27%, Cr accounts for 10-14%, and N accounts for 59-67% in terms of atomic percentage;
[0049] In the TiAlSiCuN coating, according to atomic percentage, Ti accounts for 18-20%, Al accounts for 35-39%, Si accounts for 5-8%, Cu accounts for 6-8%, and N accounts for 25-36%.
[0050] Using TiAlSiCuN and AlCrN coatings as one of the nanocomposite coatings can effectively improve the film-substrate bonding strength and thermal stability of the coating. The AlCrN coating can optimize the deposition environment, which can not only provide better bonding strength for the deposition of the TiAlSiCuN coating, but also prevent the elements from penetrating into the substrate under high temperature environment. The nanocomposite coating has good mechanical properties through the introduction of nanocomposite structure and Cu element. Cu element is added on the basis of TiAlSiN coating. The incorporation of Cu element plays an important role in reducing the internal pressure stress and friction coefficient of the hard coating, and can improve the oxidation resistance of the coating. Since copper nitride is unstable and copper is immiscible with titanium nitride, the copper-doped titanium nitride coating tends to embed copper nanoparticles into transition metal nitrides to form a nanocomposite structure.
[0051] As an optional embodiment of the AlCrN / TiAlSiCuN nanocomposite coating of the present invention, the thickness of the CrN transition layer is 0.1 to 0.3 μm (e.g., 0.15 μm, 0.2 μm, 0.25 μm);
[0052] and / or, the total thickness of the AlCrN coating is 1.2-1.6 μm (e.g., 1.3 μm, 1.4 μm, 1.5 μm); preferably, the thickness of the AlCrN coatings disposed at different positions is the same;
[0053] And / or, the total thickness of the TiAlSiCuN coating is 1.2-1.6 μm (such as 1.3 μm, 1.4 μm, 1.5 μm); preferably, the thickness of the TiAlSiCuN coatings arranged at different positions is the same;
[0054] And / or, in each group of AlCrN coating and TiAlSiCuN coating formed outward from the CrN transition layer, the thickness ratio of the AlCrN coating to the TiAlSiCuN coating is 1:1.
[0055] As an optional implementation of the AlCrN / TiAlSiCuN nanocomposite coating of the present invention, the TiAlSiCuN layer of the AlCrN / TiAlSiCuN nanocomposite coating forms a nanocomposite structure in which a (Ti, Al)N nanocrystalline phase is wrapped by an amorphous phase Si3N4.
[0056] According to a second aspect of the present invention, the present invention provides a method for preparing the AlCrN / TiAlSiCuN nanocomposite coating according to the first aspect, comprising the following steps:
[0057] S1. Pretreatment: grinding and polishing the substrate, cleaning it and wiping off dust;
[0058] S2. Vacuuming: Pump the pressure in the coating chamber to 3×10 -3 ~4×10 -3 Pa, then raise the temperature in the coating chamber to 480°C before starting the coating test;
[0059] S3, etching and cleaning: introduce argon gas into the coating chamber, control the pressure in the coating chamber to 0.3-1 Pa, and start particle etching;
[0060] S4, TiAlSiCuN / AlCrN / CrN layer deposition: open the argon channel to pass argon gas, then open the nitrogen channel to pass nitrogen gas, set the bias voltage to -80~120V (for example, -80V, -90V, -100V, -110V, -115V), adjust the pressure in the coating chamber to 0.8~1Pa (for example, 0.85Pa, 0.9Pa, 0.95Pa), turn on the Cr target, deposit to obtain the CrN coating, then alternately turn on the AlCr target and the TiAlSiCu target, turning on the AlCr target and the TiAlSiCu target once is counted as one cycle, the cycle is at least once, and the TiAlSiCuN / AlCrN coating is deposited;
[0061] The arrangement of the AlCrN / TiAlSiCuN nanocomposite coating of the present invention can ensure good bonding between coating layers, improve the bonding strength of the coating, and eliminate certain internal stresses, so that the coating has better hardness.
[0062] As an optional implementation of the method for preparing the AlCrN / TiAlSiCuN nanocomposite coating of the present invention, in the step S1, the substrate is any one of cemented carbide, high-speed steel, and corundum.
[0063] As an optional implementation manner of the preparation method of the AlCrN / TiAlSiCuN nanocomposite coating of the present invention, in the step S1, the grinding and polishing treatment is to grind the substrate with sandpaper until it is smooth and flat without obvious defects, and then polish it with a metallographic polishing machine until the surface of the substrate sample is mirror-like without obvious defects; and / or, the cleaning is first ultrasonic cleaning in an acetone solution, and then cleaning in ultrapure water and anhydrous ethanol; and / or, the wiping of dust is wiping with anhydrous ethanol.
[0064] As an optional implementation manner of the preparation method of the AlCrN / TiAlSiCuN nanocomposite coating of the present invention, in the step S3, the etching target is a Ti target, the current of the Ti target is 80 to 100A (for example, 85A, 90A, 95A), and the etching negative bias is -120 to -180V (for example, -130V, -140V, -150V, -160V, -170V); and / or, the particle etching time is 110 to 130min (for example, 115min, 120min, 125min); and / or, the flow rate of the argon gas is 450 to 500sccm (for example, 460sccm, 470sccm, 480sccm, 490sccm).
[0065] As an optional implementation of the method for preparing the AlCrN / TiAlSiCuN nanocomposite coating of the present invention, in the step S4, the target current of the Cr target is 80-100A (e.g., 85A, 90A, 95A); and / or, the target current of the AlCr target is 80-100A (e.g., 85A, 90A, 95A); and / or, the TiAlSiCu target is a mosaic target, and its target current is 80-100A (e.g., 85A, 90A, 95A); and / or, the flow rate of the argon gas is 40-60sccm (e.g., 45sccm, 50sccm, 55sccm), and the flow rate of the nitrogen gas is 600-800sccm (e.g., 650sccm, 700sccm, 750sccm);
[0066] And / or, the number of cycles is four.
[0067] As an optional embodiment of the method for preparing the AlCrN / TiAlSiCuN nanocomposite coating of the present invention, the AlCr target material is composed of the following components in atomic percentage: Al 70-75% (e.g., 71%, 72%, 73%, 74%) and Cr 25-30% (e.g., 26%, 27%, 28%, 29%), preferably Al 70% and Cr 30%;
[0068] And / or, the TiAlSiCu target is composed of the following components in atomic percentage: Ti18-25% (for example, 19%, 20%, 21%, 22%, 23%, 24%), Al55-65% (for example, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%), Si 8-12% (for example, 9%, 10%, 11%), Cu 8-10% (for example, 8.5%, 9%, 9.5%), preferably Ti 22%, Al 60%, Si 10%, Cu 8%.
[0069] The reason for selecting the composition ratio of the TiAlSiCu target material of the present invention is that when the Cu element content in the coating is too high, the hardness of the coating will be reduced, and the Ti element content is increased to promote the formation of the TiAlN phase, thereby indirectly affecting the hardness of the coating.
[0070] According to a third aspect of the present invention, the present invention provides use of the AlCrN / TiAlSiCuN nanocomposite coating described in the first aspect or the AlCrN / TiAlSiCuN nanocomposite coating prepared by the preparation method of the second aspect in a cutting tool.
[0071] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0072] Embodiment 1:
[0073] In the AlCrN / TiAlSiCuN nanocomposite coating prepared in this embodiment, the thickness of the CrN coating is 0.2 micrometers, the single layer thicknesses of the AlCrN coating and the TiAlSiCuN coating are both 0.35 micrometers, and the AlCrN coating and the TiAlSiCuN coating are alternately arranged 4 times.
[0074] In the CrN transition layer, Cr accounts for 46% and N accounts for 54% in terms of atomic percentage;
[0075] In the AlCrN coating, Al accounts for 24%, Cr accounts for 13%, and N accounts for 63% in terms of atomic percentage;
[0076] In the TiAlSiCuN coating, in terms of atomic percentage, Ti accounts for 18%, Al accounts for 35%, Si accounts for 5%, Cu accounts for 8%, and N accounts for 34%.
[0077] The specific method is as follows:
[0078] (1) Pretreatment: Cemented carbide is used as the matrix. Cemented carbide and high-speed steel can be used to characterize mechanical properties (bonding force, hardness, elastic modulus) and friction properties, and corundum can be used to characterize thermodynamic properties. Before the experiment, the matrix needs to be ground and polished. Use 300 mesh, 600 mesh, 850 mesh, 1200 mesh, and 1500 mesh sandpaper to grind the surface of cemented carbide and high-speed steel until it is smooth and flat without obvious defects. Then, use a metallographic polishing machine with the assistance of diamond powder to polish it to a mirror surface. After the treatment, the surface of the matrix sample should be neat and mirror-like, without obvious scratches and pits. Place the treated sample in an acetone solution for ultrasonic cleaning for 20 minutes to ensure that there is no oil stain, stain, etc. on the surface of the sample, and then clean it in ultrapure water and anhydrous ethanol for 10 minutes. Hang the treated sample on the rotating rack of the coating machine, wipe the dust with anhydrous ethanol again, close the furnace door, and vacuum it.
[0079] (2) Vacuuming: Open the roughing pump and roughing valve to pump the pressure in the coating chamber to below 3 Pa, then turn on the molecular pump. After the molecular pump speed stabilizes, open the fine pump and fine valve to pump to 3×10 -3 Turn on the heating module and raise the temperature in the coating chamber to 480°C. Wait until the vacuum pressure in the furnace stabilizes at 3×10 -3 Pa, coating can begin.
[0080] (3) Etching and cleaning: the argon flow rate is 450 sccm, the pressure in the coating chamber is controlled to be 0.3 Pa, the etching target (Ti target) is turned on, the Ti target current is 80 A, the etching negative bias voltage is -120 V, and particle etching is performed for 120 min.
[0081] (4) TiAlSiCuN / AlCrN / CrN layer deposition: open the argon channel, and introduce argon at a flow rate of 50 sccm. Open the nitrogen channel and fill in nitrogen at a flow rate of 300 sccm. Open the bias voltage and set the bias voltage to -120 V. Adjust the pressure in the coating chamber to 0.8 Pa. Open the Cr target with a target current of 100 A and deposit for 20 min. Then alternately open the AlCr target and the TiAlSiCu target, where the AlCr target current is 100 A and the TiAlSiCu target current is 100 A. The deposition time is 15 min. Cr is used as the bottom layer and is only turned on once. The Cr target current is turned on for 20 minutes, the AlCr target is turned on for 15 minutes each time, and the TiAlSiCu target is turned on for 15 minutes each time. This is repeated four times, during which 50 sccm of argon and 600 sccm of nitrogen are introduced. The AlCr target material used is composed of 70% Al and 30% Cr in atomic percentage, and the TiAlSiCu target material is composed of 22% Ti, 60% Al, 10% Si, and 8% Cu in atomic percentage. TiAlSiCuN / AlCrN / CrN coatings are obtained after alternating deposition. The modulation period is set to 700nm, and four cycles of deposition are performed. The thickness of the CrN coating is 0.2 microns, and the single-layer thicknesses of the AlCrN coating and the TiAlSiCuN coating are both 0.35 microns.
[0082] (5) End of deposition: After the deposition of the CrN coating is completed, the Cr target current is turned off and the AlCr target current is turned on. After the deposition of the AlCrN coating is completed, the AlCr target current is turned off and the TiAlSiCu target current is turned on. After the deposition of the TiAlSiCuN coating is completed, the TiAlSiCu target current is turned off. The argon and nitrogen gas channels are turned off, the bias voltage is turned off, the heating module is turned off, and the coating chamber is allowed to stand to room temperature.
[0083] Example 2
[0084] The difference between this embodiment and embodiment 1 is that the TiAlSiCu target material used is composed of 20% Ti, 60% Al, 10% Si and 10% Cu in atomic percentage, and other preparation conditions are the same as those in embodiment 1.
[0085] Example 3
[0086] The difference between this embodiment and embodiment 1 is that the AlCrN coating and the TiAlSiCuN coating are deposited for two cycles respectively, and other preparation conditions are the same as those in embodiment 1.
[0087] Comparative Example 1:
[0088] This comparative example is a method for depositing an AlCrTiSiN / CrN composite layer. In the composite layer prepared by this method: in the CrN transition layer, in terms of atomic percentage, Cr accounts for 46% and N accounts for 54%;
[0089] In the AlCrTiSiN coating, in terms of atomic percentage, Al accounts for 17.5%, Cr accounts for 12.5%, Ti accounts for 7.5%, Si accounts for 7.5%, and N accounts for 55%;
[0090] (1) Pretreatment: The surface of the substrate sample was polished with sandpaper (300 mesh, 600 mesh, 850 mesh, 1200 mesh, 1500 mesh) in sequence, and then polished to a mirror surface on a metallographic grinder. Then, ultrasonic cleaning was performed in acetone, ultrapure water, and anhydrous ethanol solutions, respectively.
[0091] (2) Glow discharge and bombardment cleaning: Evacuate the coating chamber where the sample is placed to 3×10 -3 Pa and heated to 480℃. 400sccm of argon gas was introduced, and the throttle valve was adjusted to make the deposition pressure reach 2.4pa. A negative bias voltage was applied, the negative bias voltage was -800V, the frequency was 10KHz, the pulse width was 6s, the timing was 20min, and the glow cleaning was performed for 20min. The argon flow rate was adjusted to 200sccm, the throttle valve was adjusted to ensure that the deposition pressure in the coating chamber was 0.5Pa, the Cr target current was turned on at 100A, and the pulse bias voltages were set to -800V, -600V, -400V, and -200V in sequence, with an interval of 30s for each segment.
[0092] (3) Deposition of CrN transition layer: The argon flow rate is 40 sccm, the nitrogen flow rate is 250 sccm, the throttle valve is adjusted to ensure that the deposition pressure in the coating chamber is 0.8 Pa, the pulse bias is set to -80 V, the Cr target current is 80 A, and the deposition time is 20 min.
[0093] (4) Deposition of AlCrTiSiN layer: The nitrogen flow rate is 400 sccm, the argon flow rate is 80 sccm, and the throttle valve is adjusted to ensure that the deposition pressure in the coating chamber is 2.2 Pa. The pulse bias voltage is set to -120 V, the AlCrSi target current is 100 A, the AlTiSi target current is 80 A, and the deposition time is 120 min.
[0094] (5) End of deposition: turn off the current of the AlCrSi target and AlTiSi target, turn off the argon and nitrogen gas channels, turn off the bias voltage, and let the coating chamber stand to room temperature.
[0095] Comparative Example 2
[0096] The atomic percentage content of Cu in the Ti-Al-Si-Cu alloy target for preparing the TiAlSiCuN coating is 6%. The TiAlSiCu target material used is composed of atomic percentages of Ti 22%, Al 62%, Si 10%, and Cu 6%. Other preparation conditions are the same as those in Example 1.
[0097] Comparative Example 3
[0098] The atomic percentage content of Cu in the Ti-Al-Si-Cu alloy target for preparing the TiAlSiCuN coating is 12%. The TiAlSiCu target material used is composed of atomic percentages of Ti 18%, Al 60%, Si 10%, and Cu 12%. Other preparation conditions are the same as those in Example 1.
[0099] Comparative Example 4
[0100] The coating is a TiAlSiCuN / AlCrN coating, excluding a CrN coating, and other preparation conditions are the same as those in Example 1.
[0101] Comparative Example 5
[0102] The coating is a TiAlSiCuN / CrN coating, excluding the AlCrN coating, and other preparation conditions are the same as those in Example 1.
[0103] Performance Testing
[0104] The hardness was tested by nanoindentation instrument;
[0105] The elastic modulus E was measured using a nanoindenter;
[0106] The bonding strength was tested using a nano scratch tester;
[0107] The friction coefficient was tested by a thermal friction and wear testing machine.
[0108] Performance data
[0109] Figure 1 The schematic diagram of the structure of TiAlSiCuN / AlCrN / CrN coating shows that the TiAlSiCuN and AlCrN coatings can effectively improve the film-substrate bonding strength and thermal stability of the coatings as nanocomposite coatings. The AlCrN coating can optimize the deposition environment, which can not only provide better bonding strength for the deposition of the TiAlSiCuN coating, but also prevent the elements from penetrating into the substrate under high temperature environment. The nanocomposite structure and the introduction of Cu element make the nanocomposite coating have good mechanical properties.
[0110] Figure 2 The surface morphology of the TiAlSiCuN / AlCrN / CrN coating is shown in the figure. It can be seen that the surface of the TiAlSiCuN / AlCrN / CrN coating is relatively flat and dense, but there are still some large particles and pits, which are caused by the arc ion plating equipment. When the target is energized, the sputtered particles are sputtered to the substrate surface under the support of bias voltage, and a large number of droplets are sputtered to the substrate surface for deposition, thereby forming large particles, and the unevenly distributed surface stress promotes the formation of pits.
[0111] Table 1 is a comparison of the hardness, elastic modulus, bonding force and friction coefficient of TiAlSiCuN coating and AlCrTiSiN coating:
[0112] Table 1
[0113]
[0114] As can be seen from Table 1, compared with the AlCrTiSiN coating, the hardness of the TiAlSiCuN / AlCrN / CrN coating remains basically unchanged, the elastic modulus decreases, the soft Cu enters the coating, and the internal compressive stress of the hard coating is reduced. The ratio of hardness to elastic modulus can characterize the toughness of the coating material to a certain extent. The larger the ratio, the better the toughness of the coating material. The H / E value of the TiAlSiCuN / AlCrN / CrN coating is higher than that of the AlCrTiSiN coating, indicating that the TiAlSiCuN / AlCrN / CrN nanocomposite coating of the present invention maintains the hardness basically unchanged while taking into account the coordination of toughness; the bonding force of the TiAlSiCuN / AlCrN / CrN coating is also higher than that of the comparative example, which is due to the strong film-base bonding strength between the AlCrN layer and the coating and the CrN adjusting the thermal expansion coefficient between the substrate and the coating.
[0115] Figure 3 The friction coefficient of TiAlSiCuN / AlCrN / CrN coating is compared with that of AlCrTiSiN coating. As shown in the figure, the anti-friction ability of TiAlSiCuN / AlCrN / CrN coating is much higher than that of comparative example 1. This is because Cu and TiAlN are immiscible, and the Cu-doped TiAlN coating tends to embed copper nanoparticles into the transition metal nitride matrix to form a nanocomposite structure, which plays a lubricating role. During the tool cutting process, a large amount of heat will be released, and the TiAlSiCuN / AlCrN / CrN coating can still provide good self-lubricating performance in a high temperature environment.
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An AlCrN / TiAlSiCuN nanocomposite coating, characterized in that: The composite coating is coated on a substrate, and includes, from the surface of the substrate outward, a CrN transition layer, and an AlCrN coating and a TiAlSiCuN coating that are alternately arranged; The AlCrN coating and the TiAlSiCuN coating are at least one layer respectively; In the CrN transition layer, Cr accounts for 45-50% and N accounts for 50-55% in terms of atomic percentage; In the AlCrN coating, Al accounts for 23-27%, Cr accounts for 10-14%, and N accounts for 59-67% in terms of atomic percentage; In the TiAlSiCuN coating, according to atomic percentage, Ti accounts for 18-20%, Al accounts for 35-39%, Si accounts for 5-8%, Cu accounts for 6-8%, and N accounts for 25-36%.
2. The AlCrN / TiAlSiCuN nanocomposite coating according to claim 1, characterized in that: The thickness of the CrN transition layer is 0.1-0.3 μm; And / or, the total thickness of the AlCrN coating is 1.2-1.6 μm; preferably, the thickness of the AlCrN coatings disposed at different positions is the same; And / or, the total thickness of the TiAlSiCuN coating is 1.2-1.6 μm; preferably, the thickness of the TiAlSiCuN coatings arranged at different positions is the same; And / or, in each group of AlCrN coating and TiAlSiCuN coating formed outward from the CrN transition layer, the thickness ratio of the AlCrN coating to the TiAlSiCuN coating is 1:
1.
3. The AlCrN / TiAlSiCuN nanocomposite coating according to claim 1, characterized in that: The TiAlSiCuN layer of the AlCrN / TiAlSiCuN nanocomposite coating forms a nanocomposite structure in which a (Ti, Al)N nanocrystal phase is wrapped by an amorphous phase Si3N4.
4. A method for preparing the AlCrN / TiAlSiCuN nanocomposite coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Pretreatment: Grind and polish the substrate, clean and wipe off dust; S2. Vacuuming: Pump the pressure in the coating chamber to 3×10 -3 ~4×10 -3 Pa, and then the temperature in the coating chamber is raised to 480°C before coating begins; S3, etching and cleaning: introduce argon gas into the coating chamber, control the pressure in the coating chamber to 0.3-1 Pa, turn on the etching target to etch particles; S4. TiAlSiCuN / AlCrN / CrN layer deposition: open the argon channel to pass argon gas, then open the nitrogen channel to pass nitrogen gas, set the bias voltage to -80~120V, adjust the pressure in the coating chamber to 0.8~1Pa, turn on the Cr target, deposit to obtain a CrN coating, then alternately turn on the AlCr target and the TiAlSiCu target, turning on the AlCr target and the TiAlSiCu target once each is counted as one cycle, the cycle is at least once, and a TiAlSiCuN / AlCrN nanocomposite coating is deposited.
5. The method for preparing the AlCrN / TiAlSiCuN nanocomposite coating according to claim 4, characterized in that: In the step S1, the substrate is any one of cemented carbide, high speed steel and corundum.
6. The method for preparing the AlCrN / TiAlSiCuN nanocomposite coating according to claim 4, characterized in that: In the step S1, the grinding and polishing treatment is to use sandpaper to grind the substrate until it is smooth and flat without obvious defects, and then use a metallographic polishing machine to polish until the surface of the substrate sample is mirror-like without obvious defects; and / or, the cleaning is first ultrasonic cleaning in an acetone solution, and then cleaning in ultrapure water and anhydrous ethanol; and / or, the wiping of dust is wiping with anhydrous ethanol.
7. The method for preparing the AlCrN / TiAlSiCuN nanocomposite coating according to claim 4, characterized in that: In step S3, the etching target is a Ti target, the current of the Ti target is 80-100A, and the negative etching bias voltage is -120--180V; and / or, the particle etching time is 110-130min; and / or, the flow rate of the argon gas is 450-500sccm.
8. The method for preparing the AlCrN / TiAlSiCuN nanocomposite coating according to claim 4, characterized in that: In the step S4, the target current of the Cr target is 80-100A; and / or, the target current of the AlCr target is 80-100A; and / or, the TiAlSiCu target is a mosaic target, and its target current is 80-100A; and / or, the flow rate of the argon gas is 40 to 60 sccm, and the flow rate of the nitrogen gas is 600 to 800 sccm; And / or, the number of cycles is four.
9. The method for preparing the AlCrN / TiAlSiCuN nanocomposite coating according to claim 4, characterized in that: The AlCr target material is composed of the following atomic percentages: Al 70-75% and Cr 25-30%, preferably Al 70% and Cr 30%; And / or, the TiAlSiCu target material is composed of the following components in atomic percentage: Ti 18-25%, Al 55-65%, Si 8-12%, Cu 8-10%, preferably Ti 22%, Al 60%, Si 10%, Cu 8%.
10. Use of the AlCrN / TiAlSiCuN nanocomposite coating according to any one of claims 1 to 3 or the AlCrN / TiAlSiCuN nanocomposite coating prepared by the preparation method according to any one of claims 4 to 9 in cutting tools.